Evaluation of the efficacy of antifungal drugs against Paracoccidioides brasiliensis and Paracoccidioides lutzii in a Galleria mellonella model - de Lacorte Singulani, Junya [UNESP]; Scorzoni, Liliana [UNESP]; de Paula e Silva, Ana Carolina Alves [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Elsevier, 2016)
Paracoccidioides brasiliensis and P. lutzii belong to a group of thermodimorphic fungi and cause paracoccidioidomycosis (PCM), which is a human systemic mycosis endemic in South and Central America. Patients with this mycosis are commonly treated with amphotericin B (AmB) and azoles. The study of fungal virulence and the efficacy and toxicity of antifungal drugs has been successfully performed in a Galleria mellonella infection model. In this work, G. mellonella larvae were infected with two Paracoccidioides spp. and the efficacy and toxicity of AmB and itraconazole were evaluated in this model for the first time. AmB and itraconazole treatments were effective in increasing larval survival and reducing the fungal burden. The fungicidal and fungistatic effects of AmB and itraconazole, respectively, were observed in the model. Furthermore, these effects were independent of changes in haemocyte number. G. mellonella can serve as a rapid model for the screening of new antifungal compounds against Paracoccidioides and can contribute to a reduction in experimental animal numbers in the study of PCM.
Keywords: Alternative animal model; Antifungals; Efficacy; Paracoccidioidomycosis